2017
DOI: 10.1051/0004-6361/201731230
|View full text |Cite
|
Sign up to set email alerts
|

Pulsating low-mass white dwarfs in the frame of new evolutionary sequences

Abstract: Context. Many pulsating low-mass white dwarf stars have been detected in the past years in the field of our Galaxy. Some of them exhibit multiperiodic brightness variation, therefore it is possible to probe their interiors through asteroseismology. Aims. We present a detailed asteroseismological study of all the known low-mass variable white dwarf stars based on a complete set of fully evolutionary models that are representative of low-mass He-core white dwarf stars. Methods. We employed adiabatic radial and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 82 publications
0
38
0
Order By: Relevance
“…Hence, there may be only four likely pulsating ELM WDs: the three pulsators presented in Hermes et al (2013b) and the WD companion to PSR J1738+0333 . Measuring the rate of pulsation period change could clarify their stellar nature, because different classes of pulsators have different rates of period change (Calcaferro et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Hence, there may be only four likely pulsating ELM WDs: the three pulsators presented in Hermes et al (2013b) and the WD companion to PSR J1738+0333 . Measuring the rate of pulsation period change could clarify their stellar nature, because different classes of pulsators have different rates of period change (Calcaferro et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…We close this section by briefly describing the first attempts of asteroseismology of ELMV stars. A detailed asteroseismological study of all the known and suspected ELMV stars based on the low-mass He-core WD models of Althaus et al (2013) was presented by Calcaferro et al (2017b). Despite ELMVs exhibiting very few periods and the period-to-period fits showing multiple solutions, they found that it is still possible to find asteroseismological models with M ⋆ and T eff compatible with the values derived by spectroscopy for most cases.…”
Section: Elmv and Pre-elmv Starsmentioning
confidence: 96%
“…The second asteroseismological approach for WDs was developed at La Plata Observatory and is based on non-static WD evolutionary models that result from the complete evolution of the progenitor stars. This method has been already applied to GW Virginis stars (see, e.g., Córsico et al, 2007aCórsico et al, ,b, 2008Córsico et al, , 2009aCalcaferro et al, 2016, and references therein), to DBV WDs (see, e.g., Córsico et al, 2012aCórsico et al, , 2014Bognár et al, 2014), and recently to ELMV stars (Calcaferro et al, 2017b(Calcaferro et al, , 2018b. Regarding ZZ Ceti stars, this approach has been employed by Romero et al (2012Romero et al ( , 2013Romero et al ( , 2017.…”
Section: Asteroseismic Approachesmentioning
confidence: 99%
“…And then we assumed that the envelope structure of these ELM WDs is similar to that of ELM WDs with the same mass from RL channel. If we overestimate the envelope thickness of ELM WDs from the CE channel, then some systems would not be detected by optical telescope, due to the large surface gravity and low luminosity (Calcaferro et al 2017). The combination of the EM and GW observations are expect to give a constraint of the envelope structure of ELM WDs from the CE channel.…”
Section: The Uncertainties In the Ce Processmentioning
confidence: 99%